Preliminary phytochemical screening of Chromolaena odorata: a non-native aromatic plant species at Ayer Hitam Forest Reserve, Selangor - Jumaat, Siti Rahimah; Alimuddin, E.W.; Lee, Shiou Yih; Adam, Aimi Zafirah; Mohamed, Rozi (Forestry Department Peninsular Malaysia, 2017)
Chromolaena odorata (L.) R.M. King & H. Rob (Asteraceae) is an invasive tropical plant species of America origin. In Malaysia, it can be found in open areas including plantations and at the margins of forests including at the Ayer Hitam Forest Reserve (AHFR) in Selangor. Despite being an aggressive colonizer, C. odorata has medicinal properties and a pleasant aroma especially in the leaves. Using solvents of different polarities, phytochemicals were extracted from the leaves and separated using Thin Layer Chromatography (TLC). TLC profiling indicated the presence of different groups of phytochemicals including flavonoids, terpenes, and phenolic compounds. In conclusion, C. odorata contains a considerable amount of aromatic compound, which potentially could be used in the fragrance industry.